Penerimaan diri pada mahasiswa dengan anhedonia - Oktavia, Shefhira Amanda; Setiawan, Antonius Ian Bayu (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Self-acceptance plays an important role for individuals who experience psychological disorders including anhedonia. This is because if individuals have high self-acceptance, it will have an impact on themselves in accepting the conditions experienced. The problem in this study is how self-acceptance in students with anhedonia and what factors support self-acceptance in students with anhedonia. This study aims to (1) determine self-acceptance in students with anhedonia. (2) find out the factors that support self-acceptance in college students with anhedonia. This research uses a qualitative method with a case study approach. The research was conducted in a place that had been agreed upon with the subject. The source of research data is students with anhedonia, totaling 2 people. Data collection techniques are carried out in combination using interview and observation methods. Based on the results of the research conducted, it is known that both subjects have good self-acceptance. Both subjects go through different experiences at each stage of self-acceptance. Both subjects are currently at the friendship stage, this is evidenced by both having the ability to find meaning and happiness in their lives. Each subject has supporting factors for self-acceptance that are different from one another.